2003
DOI: 10.1046/j.1439-0426.2003.00451.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of several organic acids on the feeding behavior of Tilapia nilotica

Abstract: SummaryAutomatic recording of the frequency of feeding ÔbitesÕ was used to evaluate the effects of several organic acids (citric, metacectonic, lactic, acetic, and oxalic) on the stimulatory feeding behavior of Tilapia nilotica. Some of these acids are added to food stocks to retard spoilage. The results showed that citric acid at a concentration of 10 )2 to 10 )6 M M, metacetonic acid at 10 )4 to 10 )6 M M, and lactic acid at 10 )2 to 10 )5 M M stimulated feeding. Fish tended to avoid metacetonic acid at 10 )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 5 publications
3
21
1
Order By: Relevance
“…Xie et al . () also observed a positive stimulating effect of dietary citric (10 −2 –10 −6 m ), propionic (10 −4 –10 −6 m ) and lactic acids (10 −2 –10 −5 m ) on the feeding responses of juvenile Nile tilapia, while dietary 10 −3 m acetic and propionic acids had repulsive effects. A study with Pacific white shrimp showed that among various Na salts of organic acids (formate, acetate, propionate, lactate, butyrate and citrate), the supplementation of propionate and butyrate salts to a commercial shrimp diet at 2 g kg −1 acted as feed attractants and significantly enhanced feed intake (Silva et al .…”
Section: Mode Of Action and Effects Of Dietary Organic Acidsmentioning
confidence: 80%
“…Xie et al . () also observed a positive stimulating effect of dietary citric (10 −2 –10 −6 m ), propionic (10 −4 –10 −6 m ) and lactic acids (10 −2 –10 −5 m ) on the feeding responses of juvenile Nile tilapia, while dietary 10 −3 m acetic and propionic acids had repulsive effects. A study with Pacific white shrimp showed that among various Na salts of organic acids (formate, acetate, propionate, lactate, butyrate and citrate), the supplementation of propionate and butyrate salts to a commercial shrimp diet at 2 g kg −1 acted as feed attractants and significantly enhanced feed intake (Silva et al .…”
Section: Mode Of Action and Effects Of Dietary Organic Acidsmentioning
confidence: 80%
“…Fig was known to contain some organic acids such as citric, succinic and tartaric acids (Kim, Lee, Oh & Chung 1992; Kang, Chung & Chung 1994), and dietary supplementation of some organic acids, such as citric, metacetonic and acetic acids improved the storage time and feed utilization (Kumar, Kaller, Bhaskar, Bhandary, Antony, Raju & Biradar 1997; Sugiua, Dong & Hardy 1998). Similarly, Xie, Zhang and Wang (2003) reported that dietary inclusion of citric acid at a concentration of 10 −6 –10 −2 had stimulatory effect on feeding behaviour of Tilapia nilotica .…”
Section: Ingredient Of the Experimental Dietsmentioning
confidence: 88%
“…The positive effects of LA on beluga growth might arise from the improved digestion of phosphorus from phytic acid due to the increase in intestinal acidity, which would increase the solubility of phosphorus and phytic acid, consequently enhancing the phosphorus absorption at the distal intestine (Ravindran & Kornegay, 1993). It should also be noted that Xie et al (2003) reported that LA improved the palatability of the diet, improved feed consumption and increased the apparent digestibility of nutrients in tilapia. In our study, the addition of 20g/kg LA had a positive effect on beluga growth, although this did not compensate for the negative effects of 700g/kg SBM.…”
Section: Discussionmentioning
confidence: 99%
“…One of the best additives to achieve this goal is lactic acid (LA). Xie, Zhang, and Wang () demonstrated that LA increased the appetite of the Nile tilapia Oreochromis niloticus , and several studies have shown positive effects of LA on the growth of fish and in increasing the bacterial flora in the gut (Hoseinifar, Ringø, Shenavar Masouleh, & Esteban, ; Sugiura, Gabaudan, Dong, & Hardy, ; Vielma, Mäkinen, Ekholm, & Koskela, ).…”
Section: Introductionmentioning
confidence: 99%